Obstructive sleep apnoea and cardiovascular diseases - Tażbirek, Maciej; Pierzchała, Władysław (Przewodnik Lekarza/Guide for GPs, 2010)
Obstructive sleep apnoea syndrome (SAS) is an accepted cause of life quality worsening and life expectancy shortening. Cardiovascular incidents are the mane reason of mortality in not treated properly SAS patients. The most important are: sympatic activation, endothelium dysfunction, oxidative stress, inflammation, rheological properties of blood. Current data support thesis, that SAS is connected with acute (stroke, myocardial infarction, sudden nocturnal cardiac death) and chronic (hypertension, ischemic cardiac disease, arrhythmias) cardiovascular incidents.